Prevalence and Risk Factors of Sensory Symptoms in Diabetes Patients in Taiwan - Tseng, Chin-Hsiao; Chong, Choon-Khim; Sheu, Jau-Jiuan (Frontiers in Endocrinology, 2021)
Background: Diabetic sensory neuropathy has rarely been studied in the Asian populations. This study investigated the prevalence and risk factors of sensory symptoms (SS) in the Taiwanese diabetes patients. Methods: A total of 1400 diabetes patients received a health examination together with a structured questionnaire interview for 3 categories of abnormal sensation of numbness or tingling pain, electric shock and skin thickness sensation on 7 anatomical sites on upper limbs and 6 sites on lower limbs. Prevalence of SS was defined using 9 different criteria, with the least stringent criterion of “any positive symptom on at least 1 site” and the most stringent criterion of “any positive symptom on at least bilateral and symmetrical 2 sites involving the lower limb”. Logistic regression was used to estimate the odds ratios and their 95% confidence interval for SS by the different definitions. Fasting plasma glucose and hemoglobin A1c were entered in separate models to avoid hypercollinearity. Results: The prevalence of SS was 14.4% and 54.0% when using the most stringent and least stringent criterion, respectively. Women consistently had a significantly higher prevalence than men did. Among the 3 categories of symptoms, numbness or tingling pain was the most common, and fingers and toes were the most commonly involved anatomical sites. For any symptoms, 37.1% of the patients had any symptoms on the upper limbs and 41.7% had any symptoms on the lower limbs. Female sex, diabetes duration, hemoglobin A1c and hypertension were associated with SS in all models. Conclusions: Taiwanese diabetes patients may have a high prevalence of SS if a structured questionnaire is used for screening. Female sex, diabetes duration, hemoglobin A1c and hypertension are associated with SS.